2007
DOI: 10.1007/s11095-007-9243-2
|View full text |Cite
|
Sign up to set email alerts
|

Dosage Form Development, in Vitro Release Kinetics, and in Vitro–in Vivo Correlation for Leuprolide Released from an Implantable Multi-reservoir Array

Abstract: Reproducible releases of a stable solid leuprolide formulation from a multi-reservoir microchip were achieved in vitro. Chronic pulsatile release was subsequently performed in vivo. Comparison of in vitro and in vivo data reveals that pharmacokinetics were controlled by the rate of release from the device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…The fully assembled devices included a drug filled array, microprocessor, implantable battery, and wireless antenna in a titanium housing that measured 4.5 × 5.5 × 1 cm 3 with a volume of ~ 30 ml. Initial studies with leuprolide formulated at 100 mg/ml and filled into 300 nl reservoirs showed good stability and an excellent in vitro-in vivo release rate correlation [98]. Similarly, an osteoporosis implant delivering pulsatile parathyroid hormone (PTH) was formulated at 500 mg/ml (~ 20 μg PTH/reservoir) and demonstrated good stability after 6 months at 37°C (Fig.…”
Section: Implantable Deliverymentioning
confidence: 99%
“…The fully assembled devices included a drug filled array, microprocessor, implantable battery, and wireless antenna in a titanium housing that measured 4.5 × 5.5 × 1 cm 3 with a volume of ~ 30 ml. Initial studies with leuprolide formulated at 100 mg/ml and filled into 300 nl reservoirs showed good stability and an excellent in vitro-in vivo release rate correlation [98]. Similarly, an osteoporosis implant delivering pulsatile parathyroid hormone (PTH) was formulated at 500 mg/ml (~ 20 μg PTH/reservoir) and demonstrated good stability after 6 months at 37°C (Fig.…”
Section: Implantable Deliverymentioning
confidence: 99%
“…In previous studies, a high leuprolide concentration formulation used in combination with a similar multi-reservoir device demonstrated very good in vitro-in vivo correlation, indicating that the rate limitation for delivery is the solubility and diffusion of the formulation from the reservoir (21). The rapid, pulsatile in vitro release data presented here for hPTH suggests similar (desirable) pharmacokinetics may be observed in vivo, but in vivo experiments have not yet been performed.…”
Section: Discussionmentioning
confidence: 64%
“…Each array contains 24 reservoirs with a volumetric capacity of 300 nL per reservoir (21). Individual reservoirs of the multi-reservoir array were filled with 200 nL of the concentrated hPTH(1-34) solution(s) using an automated dispensing apparatus.…”
Section: Reservoir Fillingmentioning
confidence: 99%
See 2 more Smart Citations